Determinants of Utilization of Maternal Healthcare Services in Ethiopia - Melese, Wondiber Nega; Darak, Shirnevas; Tefera, Mesay (International Journal of Statistics in Medical Research, 2015)
Utilizing maternal healthcare services, such as antenatal care, professionals’ assistance during delivery and postnatal care contributes significant role in reduction of maternal and child mortality. However, there are many factors both at individual and community level that affect utilization of these required services. To determine the levels of effects of socio-economic and demographic factors on uses of Maternal Healthcare services 7764 women who had given birth at least one times have taken from the 2011 Ethiopian DHS. The results showed that the rate of safe motherhood practices among reproductive age group of women in Ethiopia were too low. About 51 percent of them did not use any health care services during pregnancy, childbirth, and post-delivery periods. As WHO recommend only 6.9 percent of women were attending ANC at least four times, assisted by health professional during delivery and received PNC. The result of logistic regression showed that antenatal care, skilled delivery and postnatal care utilizations were commonly influenced by place of residence, wealth status, women’s and husband’s education and parity. Whereas, mother’s working status and husband’s education were found to be uniquely influence the uses of ANC and PNC services, respectively. In addition, both religious affiliation and age of women were also prominent predictors on utilization of ANC and uses of skilled assistance during delivery. Based on these significant factors, it is important to design and promote uses of maternal healthcare services in order to minimize the risk of maternal and child mortality.